Computational analysis of optically controlled reconfigurable terahertz mesh filters using mesa arrays. Issue 7 (16th March 2021) - Deng, Yijing; Shi, Yu; Fay, Patrick; Liu, Lei
Abstract: We report a novel approach for realizing tunable/reconfigurable terahertz (THz) mesh filters on the basis of micromachined mesa‐array structures. In this approach, different filter patterns are generated virtually using photogenerated free carriers in a semiconducting mesa‐array structure to achieve superior tunability and reconfigurability. Micromachined mesa‐array structures enable the formation of high fidelity, optically generated mesh filter structures for THz frequencies. To evaluate the proposed filter designs, the optically patterned spatial modulation properties of mesa‐array structures were first evaluated. Reconfigurable mesh filter prototypes were then designed and simulated using silicon mesa arrays with 50 × 50 μm 2 square mesa unit cells. Simulations show that reconfigurable bandpass filters (BPFs) operating in the frequency range of 108–489 GHz with insertion losses of 0.82–1.13 dB can be achieved. By employing smaller unit cells, the frequency tuning range and filtering performance can be further improved. In addition to BPFs, other filter functionalities can also be realized utilizing the proposed approach. The wide tuning range and reconfigurability of the mesh filters demonstrate that the proposed approach is promising for developing tunable/reconfigurable circuits and components for advanced THz sensing, imaging, and communications.